UPAYA PENINGKATAN LITERASI WAKAF TUNAI DI PONDOK PESANTREN - Setyo Tri Wahyudi; Dwi Retno Widiyanti (CV. Multi Kreasi Media, 2022)
Literacy activities in the financial sector, especially those related to cash waqf from community, by community, and for the community are carried out by BWI, the Ministry of Finance, and also the campus to the community, in order to realize the potential of waqf in Indonesia of Rp180 trillion. There are several main challenges in developing the potential of cash waqf in Indonesia in addition to governance challenges, including the low literacy of the Indonesian people about cash waqf and limited financial instruments in developing the value (assets) of cash waqf. The National Waqf Literacy Index (ILW) value overall got a score of 50.48 which was included in the low category, consisting of the Basic Waqf Understanding Literacy Value of 57.67 and the Advanced Waqf Understanding Literacy Value of 37.97. The people of East Java province are included in the group of regions that have ILW scores in the medium category which tend to be low. By using a workshop method approach for pesantren, this Community Service program is expected to be able to increase the literacy rate of cash waqf in the pesantren environment in Jabung District, Malang Regency, East Java.